Nature of MoH···I bonds in Cp2Mo(L)H···I‐C≡C‐R Complexes (L=H, CN, PPh2, C(CH3)3; R=NO2, Cl, Br, H, OH, CH3, NH2). (11th January 2018) - Dang, Yaru; Wang, Weihua; Meng, Lingpeng; Li, Qingzhong; Li, Xiaoyan
Abstract : The nature of the MoH···I bond in Cp2 Mo(L)H···I‐C≡C‐R (L= H, CN, PPh2, C(CH3 )3 ; R=NO2, Cl, Br, H, OH, CH3, NH2 ) was investigated using electrostatic potential analysis, topological analysis of the electron density, energy decomposition analysis and natural bond orbital analysis. The calculated results show that MoH···I interactions in the title complexes belong to halogen‐hydride bond, which is similar to halogen bonds, not hydrogen bonds. Different to the classical halogen bonds, the directionality of MoH···I bond is low; Although electrostatic interaction is dorminant, the orbital interactions also play important roles in this kind of halogen bond, and steric interactions are weak; the strength of H···I bond can tuned by the most positive electrostatic potential of the I atom. As the electron‐withdrawing ability of the R substituent in the alkyne increases, the electrostatic potential maximum of the I atom increases, which enhances the strength of the H···I halogen bond, as well as the electron transfer. Abstract : In contrast to classical halogen bonds, the MoH···I bond is lowly directional and orbital interaction is important.